The supportive care needs of people living with pulmonary fibrosis and their caregivers: a systematic review. (29th April 2020) - Lee, Joanna Y.T.; Tikellis, Gabriella; Corte, Tamera J.; Goh, Nicole S.; Keir, Gregory J.; Spencer, Lissa; Sandford, Debra; Khor, Yet H.; Glaspole, Ian; Price, John; Hey-Cunningham, Alison J.; Maloney, Jamie; et al.
Background: People with pulmonary fibrosis often experience a protracted time to diagnosis, high symptom burden and limited disease information. This review aimed to identify the supportive care needs reported by people with pulmonary fibrosis and their caregivers. Methods: A systematic review was conducted according to PRISMA guidelines. Studies that investigated the supportive care needs of people with pulmonary fibrosis or their caregivers were included. Supportive care needs were extracted and mapped to eight pre-specified domains using a framework synthesis method. Results: A total of 35 studies were included. The most frequently reported needs were in the domain of information/education, including information on supplemental oxygen, disease progression and prognosis, pharmacological treatments and end-of-life planning. Psychosocial/emotional needs were also frequently reported, including management of anxiety, anger, sadness and fear. An additional domain of "access to care" was identified that had not been specified a priori ; this included access to peer support, psychological support, specialist centres and support for families of people with pulmonary fibrosis. Conclusion: People with pulmonary fibrosis report many unmet needs for supportive care, particularly related to insufficient information and lack of psychosocial support. These data can inform the development of comprehensive care models for people with pulmonary fibrosis and their loved ones. Summary of unmet care needs reported by people with pulmonary fibrosis and their caregivers across a range of settings and countries. People with pulmonary fibrosis and their caregivers have many unmet needs. The results can help improve care provided for people with pulmonary fibrosis and caregivers. http://bit.ly/39PdjfQ